Pembuatan Film Wisata Sebagai Media Promosi Pariwisata di Desa Rumah Galuh Kabupaten Langkat - Sinulingga, Samerdanta; Pardosi, Jhonson; Bangun, Nur Cahaya; Siahaan, Hotlan (Jurnal Master Pariwisata (JUMPA); Volume 06, Nomor 02, Januari 2020, 2020)
Film and tourism during the 4.0 industrial revolution now have a strategic positioning in attracting tourist visits. Because the film is able to exert a powerful influence on tourist visits, the Ministry of Tourism and Creative Economy then carries out a program that closely targets millennials as a tourist market target with the slogan 'instagramable'. Herein lies the power of film in attracting tourist visits that can be a solution for all tourist areas in Indonesia, especially for Rumah Galuh Village. At the beginning of the pioneering natural tourism in this village, the film had an extraordinary impact on the number of tourist visits. In 2016 until now, the number of tourist visits has increasingly declined. Based on these problems, research on making tourist films as promotional media is expected to be a useful breakthrough. This study uses the science of phenomenology, participant observation techniques, with data analysis: (1) data reduction; (2) data presentation; and (3) drawing conclusions / verification. The making of tourism films in this study uses 2 theories, a secondary theory, namely: the theory of film making with 3 working indicators: pre-production, production and post-production of films, while the primary theory is: film theory as a tourism promotion media with 4 working indicators: color , features, properties and ratios. The results of the application of the seven working indicators of the theory produce a true tourism film as a tourism promotion media. For our next research we recommend the effect or impact caused by the tourist film on the flow of tourist visits to these tourist destinations. Keywords: Tourism Films Making, Tourism Films as Promotional Media.